PTU-084 Long term outcomes after transition to adult services in paediatric-onset inflammatory bowel disease patients treated with anti-tnf. (22nd June 2015) - Pollington, C; Cameron, FL; Kennedy, NA; Arnott, I; Satsangi, J; Wilson, DC
Abstract : Introduction: Anti-TNF therapy use in paediatric IBD (PIBD) is increasing worldwide with evidence of short-term effectiveness and safety. Longer term outcomes are less clear due to lack of follow-up (FU) of young people after transition to adult services. We aimed to assess effectiveness and safety of anti-TNF therapy in PIBD post-transition to adult care. Method: A retrospective case review of PIBD patients treated with anti-TNF (Infliximab (IFX) or Adalimumab (ADA)) in the SE Scotland regional PIBD unit at RHSC, Edinburgh and then transitioned to the regional adult specialist IBD centre at WGH, Edinburgh, during 01/01/00–30/09/13. Data (including outcome and duration of anti-TNF therapy, dose escalation, adverse events and discontinuation/re-start of therapy) were collected prior to, at the time of transition from PIBD services, and to study end point (transfer out of region, loss to FU, death or ongoing adult care at 31/07/2014), a minimum 10 months FU. Results: 34 children (30 Crohn's disease (CD), 4 ulcerative colitis (UC)) had anti-TNF exposure in PIBD services then a median (range) duration of FU post-transition of 2.9 (0.7–9.3) years. At transition, 19/34 were still on anti-TNF (12 IFX and 7 ADA). 10/12 IFX were in steroid-free remission (SFR) and 8/10 remained in SFR at last FU; 2 discontinued IFX due to loss of response (LoR), both then had ADA with 1 ADA LoR and 1 SFR on ADA at last FU. 1/12 IFX patient with moderate disease at transition then achieved remission, had planned drug withdrawal (PDW) then relapsed, restarted IFX and had mild disease at last FU. 1/12 IFX patients had response with mild disease post-induction IFX but transitioned and had primary non-response (PNR) by 6 doses IFX, and switched to ADA with moderate disease activity at last FU. 3/7 ADA patients at transition were in SFR; 1 stopped as PDW in prolonged remission but 2 stopped due to adverse events. 2/7 ADA patients with mild disease at transition then achieved sustained remission up to last FU. 2/7 ADA patients had moderate disease at transition; one had ADA LoR and moderate disease at last FU, the other gained remission so had PDW, relapsed but was in remission at last FU. There were no deaths or malignancies associated with anti-TNF use. Conclusion: Anti-TNF therapy post-transition is effective at maintaining remission in those with remission prior to transition, although some may require a 2nd anti-TNF agent to maintain remission. Those previously not in remission can achieve sustained remission, usually if just starting anti-TNF maintenance at transition; others do not and have a more complicated disease course. Loss of response remains a key reason for stopping anti-TNF therapy. Disclosure of interest: None Declared.